RETRACTED: Dosage forms and their role in modern homeopathic practice - E. I. Sakanyan; N. D. Bunyatyan; M. N. Lyakina; N. S. Tereshina; T. B. Shemeryankina; N. A. Postoyuk (Регуляторные исследования и экспертиза лекарственных средств)
RETRACTED ARTICLEThe research related to the development of general monographs regulating the requirements for dosage forms used in homeopathic practice is of current interest. The need to harmonize the requirements for the mentioned dosage forms in Russia and abroad is evident, which indicates the reasonability of establishing national standards for the quality of dosage forms for domestic homeopathic medicines. The content of the mentioned standards should be harmonized with the requirements for dosage forms used in allopathic practice.